Implementasi Peraturan Presiden No. 31 Tahun 2015 Terhadap Sistem Transportasi Darat Pulai Sebatik - Salsabila, Nur'annisa; Mulyani, Sari (Department of International Relations, Universitas Mulawarman, 2022)
The development of a Land Transportation Network System in Sebatik Island implemented within two program, first is repair the ring road and repair the crossing port or known as Sei-Nyamuk port. Development of a Land Transportation Network System to maintain the economic and social security of the border society, thus expected will affect to the security and sovereighnty of the country on the Indonesian Sebatik Island.